2013
DOI: 10.1159/000353567
|View full text |Cite
|
Sign up to set email alerts
|

Severe Disability in Patients with Relapsing-Remitting Multiple Sclerosis Is Associated with Profound Changes in the Regulation of Leptin Secretion

Abstract: Objectives: Experimental evidences indicate that leptin is involved in the neuroinflammatory process sustaining multiple sclerosis (MS). However, the relationship between leptin and body fat, as assessed by body mass index (BMI), in MS was not previously evaluated. It was the aim of this study to compare serum leptin levels between patients with MS and healthy controls and to evaluate the possible relationship between circulating leptin levels and disease severity. Patients and Methods: Eighty-four MS patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 27 publications
2
30
1
Order By: Relevance
“…Therefore, it has been hypothesized that leptin is effective in reducing inflammation and autoimmunity seen in immune‐mediated neurological diseases, including MS . Several experimental and clinical studies support this hypothesis, reporting that the level of serum leptin was higher in patients with MS in remission compared to healthy subjects and that the level of serum leptin significantly decreased after 2 months of interferon beta treatment . These studies concluded that the increase in the level of serum leptin activates immune cells, resulting in the release of cytokines, which, in turn, further increase leptin production and finally reverse the inflammatory process in MS .…”
Section: The Role Of Leptin In Neurological Diseasesmentioning
confidence: 98%
“…Therefore, it has been hypothesized that leptin is effective in reducing inflammation and autoimmunity seen in immune‐mediated neurological diseases, including MS . Several experimental and clinical studies support this hypothesis, reporting that the level of serum leptin was higher in patients with MS in remission compared to healthy subjects and that the level of serum leptin significantly decreased after 2 months of interferon beta treatment . These studies concluded that the increase in the level of serum leptin activates immune cells, resulting in the release of cytokines, which, in turn, further increase leptin production and finally reverse the inflammatory process in MS .…”
Section: The Role Of Leptin In Neurological Diseasesmentioning
confidence: 98%
“…MS usually commences in early adulthood, with paralysis, sensory disturbances, lack of coordination and visual impairment among its most frequent features [3]. The disease often begins with an ‘attack' or ‘flare' that lasts from a few days to weeks and is followed by remission that most often lasts from a few months to years [4,5]. The variable course of the disease may be reflected in the differences seen at the morphological level by magnetic resonance imaging and histopathologic evaluations of the CNS, which also vary significantly [6].…”
Section: Introductionmentioning
confidence: 99%
“…Normal leptin levels crucially maintain and regulate the body's immune function. Emerging evidence indicates that leptin acts as a proinflammatory cytokine in immune responses such as systemic lupus erythematosus (SLE) [3][4][5][6], RA [7][8][9][10], multiple sclerosis (MS) [11][12][13] and psoriasis [14][15][16]. Leptin could be a member of the cytokine network managing the inflammatory immune response and host defence mechanisms.…”
Section: Introductionmentioning
confidence: 99%